(untitled) (Research, Society and Development, 2021)
Necrotizing enterocolitis is an inflammatory bowel disease that occurs in newborns, more commonly in preterm infants. It is the leading cause of death from gastrointestinal diseases in neonates, and is characterized by the development of diffuse intestinal necrosis in premature infants subjected to stress. The high incidence and lack of effective treatment strategies suggest that new approaches to treating the disease are needed. It is in this context that the possibility of using photobiomodulation as a therapeutic modality arises. However, studies on the use of photobiomodulation in intestinal bacteria are scarce. To study the effect of photobiomodulation used in clinical parameters on the growth of bacteria commonly present in the newborn microbiota. Four strains of bacteria were chosen to be studied, two belonging to healthy intestinal microbiota, Lactobacillus acidophilus and Lactobacillus reuteri, and two pathogenic bacteria, Escherichia coli and Staphylococcus aureus. These bacteria were cultivated in planktonic growth and irradiated with LED at a wavelength of 660 nm and a power density of 0.025 W/cm2, at fluences of 1, 5 and 10 J/cm2. The evaluation of cell growth was performed through absorbance readings in the periods of 4h, 24h and 48h after irradiation. The growth of L. acidophilus, L. reuteri and S. aureus did not undergo biomodulation in any of the fluences. The growth of E. coli was stimulated at 1 J/cm2 when compared to the Control group, with statistical significance (p<0.005). In the other fluencies there was no biostimulation for the E. coli bacteria. The use of a wavelength of 660 nm in the fluences of 5 J/cm2 and 10 J/cm2 in the studied bacteria did not lead to a significant change in the growth rate.